A facile strategy for the synthesis of a NaREF4-gold nanocomposite as a dual-modal bioimaging agent. Issue 35 (18th April 2017) - Shen, Bin; Gao, Yilin; Liu, Qingyun; Cheng, Shengming; Feng, Wei; Li, Fuyou
Abstract : A UCNP&Au@SiO2 nanocomposite synthesized by in situ reduction of HAuCl4 as a dual modality imaging agent. Abstract : In this article, a facile strategy is developed to synthesize a nanocomposite containing both a rare earth doped upconversion nanoparticle (RE-UCNP) and gold nanoparticles (GNPs). Such a nanocomposite can serve as a dual-modal imaging agent for upconversion luminescence (UCL) imaging and photoacoustic tomography (PAT). High spatial resolution, 3-dimensional imaging of blood vessels could be achieved with the RE-UCNP/GNPs@SiO2 nanocomposite by PAT, while UCL imaging offers a high-speed, low-interference and 2-dimensional imaging mode.